THE IMPACT OF VITAMIN D DEFICIENCY ON THE MANIFESTATIONS OF METABOLIC SYNDROME IN WOMEN OF REPRODUCTIVE AGE - Khasanova G.Kh., Tukhtaeva N.Kh., (Central Asian Journal of Medicine, 2025)
This prospective study included 150 outpatient women aged 16–41 years with metabolic syndrome (MS) and 25-hydroxyvitamin D [25(OH)D] levels below 30 nmol /L. All participants underwent anthropometry, bioimpedance measurement of body composition, assessment of carbohydrate and lipid metabolism parameters, and genotyping of FokI and ApaI polymorphisms of the VDR gene. The treatment protocol included daily intake of cholecalciferol at a dose of 10,000 IU, myo- inositol 4 g, and a low-carbohydrate high-fat (LCHF) diet against the background of standard MS therapy with metformin. After 12 weeks, the median 25(OH)D value reached the reference level; body mass index decreased by 7.8% (p < 0.01), waist circumference by 6.5% (p < 0.01). There was a significant decrease in HOMA-IR (–32%), triglyceride (–18%) and LDL (–11%) concentrations with a simultaneous increase in HDL (+9%). The most pronounced metabolic improvement was noted in carriers of the minor FokI -T and ApaI -C alleles. For the first time in the population of Uzbekistan, a connection between vitamin D deficiency and MS with VDR gene polymorphisms was established, and the high efficiency of complex nutraceutical correction carried out against the background of an LCHF diet was confirmed. Based on the data obtained, a screening algorithm was developed that involves mandatory determination of 25(OH)D and genetic risk markers, which allows for personalization of therapy and increases its clinical and socio-economic effectiveness.